Antidepressant and Group Psychosocial Treatment for Depression: A Rater Blind Exploratory RCT from a Low Income Country. Issue 6 (19th July 2013) - Husain, Nusrat; Chaudhry, Nasim; Fatima, Batool; Husain, Meher; Amin, Rizwana; Chaudhry, Imran Bashir; Ur Rahman, Raza; Tomenson, Barbara; Jafri, Farhat; Naeem, Farooq; Creed, Francis
Abstract : Background: Research in the West shows that group psychological intervention together with an antidepressant treatment leads to more effective treatment of a depressive disorder. There are no treatment trials from low income countries comparing the efficacy of antidepressant treatment with a group psychological intervention.Aim: To conduct a feasibility trial to compare the efficacy of an antidepressant to a group psychosocial intervention, for low income women attending primary health care in Karachi, Pakistan.Method: This was a preliminary RCT in an urban primary health care clinic in Karachi, Pakistan. Consecutive eligible women scoring >12 on the CIS-R and >18 on Hamilton Depression Rating Scale (HDRS) ( n = 66) were randomly assigned to antidepressants or a psychosocial treatment in group settings. The primary outcome measure was HDRS score; secondary outcome measures were disability and quality of life.Results: More than half of the patients in both groups improved (50% reduction in HDRS scores); at end of therapy at 3 months 19 (59.4%) vs 18 (56.2%), and at 6-month follow-up 21(67.7%) vs 20(62.5%) for antidepressants and psychosocial intervention respectively. Although HDRS, BDQ and EQ5-D scores all improved considerably in both groups from start to end of treatment, and these improvements were largely maintained after a further 3 months, the differences between the two treatments were not statistically significant.Conclusion: Psychosocial intervention was as effective as antidepressants in reducing depression and in improving quality of life and disability at the end of therapy. However, these findings need further exploration through a larger trial.